Duodenal Exclusion in the Regulation of Glycemia in Type 2 Diabetic Patients Submitted to Gastrectomy with Roux-en-Y by Gastric Cancer: Cohort Study - Franciss , Maurice Youssef (2023)
Background: The effect of the duodenal exclusion in glycemic regulation has yet to be defined. Individuals with type 2 Diabetes Mellitus (T2DM) operated for other reasons than obesity, represent an adequate model to analyze clinical outcomes of duodenal exclusion.   Objective: To analyze the changes in glycemia and pharmacotherapy for T2DM in patients undergoing gastrectomy with Roux-in-Y derivation for gastric cancer.  Methods: An observational study was conducted in 2018 on patients who were submitted to surgery from 2001 to 2016. Medical records of 129 patients’ cohort operated in two public hospitals were analyzed retrospectively before the surgery (T0) and one year after (T1). The research protocol was approved by the ethics committee. The final sample was mainly represented by women (50.5%) with a mean age of 65.5 years, and a mean body mass index of 26.5 kg/m2 SD 4.30.   Results: One year later, mean glucose levels of the entire sample decreased (p=0.046), but 70% of patients with glycemia> 100 at T0, remained with the same value in T1. Glycated hemoglobin had no significant change (p=0.988). Regarding the pharmacotherapy for T2DM, 60.7% of the sample had no change. However, 6.7% had discontinuation of the medication with the improvement of T2DM. The multivariate model by classification and decision tree method (CART) found as predictors of change in DM2 medication, age (<62.5 years) and a body mass index (> 30.2 kg/m2) with a predictive value of 71.4%.  Conclusion: There was no improvement of glycemia and pharmacotherapy in patients with T2DM who underwent gastrectomy with Roux-en-Y reconstruction, with a body mass index below 30 kg/m2